The impact of customer relationship management on finance service development - Sūdžius, Vytautas (Business: Theory and Practice, 2007)
The main objective of the article was to evaluate the customer relationship management in finance service enterprises and provide the means for improvement of this relationship. In the paper the existing quality of services and communications between enterprises and their customers is evaluated, the expert rating of enterprises quality factors is conducted and the means for customer relationship improvement in financial service enterprises are suggested. The paper revealed problems of relationship between private clients and the office staff, presented the private customers’ needs and expectations research, which helped to identify the main problems of services and enterprise’s relationship with private clients. The experts rated the main enterprises quality factors in order to propose the steps for improvement of customer relationship management. Article in Lithuanian. Ryšių su klientais valdymo poveikis finansinių paslaugų plėtrai Santrauka. Straipsnyje nagrinėjami klientų ir įmonių santykiai, jų poveikis finansinių paslaugų plėtrai. Ryšių su klientais valdymo diegimas ir plėtra yra kompleksiškai veikiami aštrėjančios konkurencijos ir globalizacijos procesų, informacines komunikacijos technologijos bei visos ekonomikos sparčių pokyčių. Įvertinus atliktus personalo ir klientų ryšių tyrimo rezultatus nustatytos neišnaudotos ryšių su klientais valdymo galimybės. Jos leidžia įmonėms, jų personalui plėtoti finansines paslaugas, geriau naudoti turimą potencialą ir išteklius, pabrėžti savo išskirtinumą ir didinti klientų lojalumą bei pasitikėjimą. Reikšminiai žodžiai: finansinės paslaugos, įmonės santykiai, poveikis, ryšiai su klientais, plėtra, valdymas.